👤

Proszę o pomoc!

(x+4)(x+4)=

(x-6)(x-6)=

(x+9)(x+9)=

(x-[tex]\frac{1}{2}[/tex])(x-[tex]\frac{1}{2}[/tex])=

(x-5)(x+5)=

(x+[tex]\frac{1}{4}[/tex])(x-[tex]\frac{1}{4}[/tex])=


Odpowiedź :

ze wzorów skróconego mnożenia

[tex]{(a-b)}^{2} = a^2-2ab+b^2\\oraz\\a^2-b^2 = (a-b)(a+b)[/tex]

(x+4)(x+4)=[tex]x^2+8x+16[/tex]

(x-6)(x-6)=[tex]x^2-12x+36[/tex]

(x+9)(x+9)=[tex]x^2+18x+81[/tex]

(x-0,5)(x-0,5)=[tex]x^2-x+0,25[/tex]

(x-5)(x+5)=[tex]x^2-25[/tex]

(x+0,25)(x-0,25)=[tex]x^2 + \frac{1}{16}[/tex]